Centrality, rapidity and transverse momentum dependence of J/ [psi] suppression in Pb-Pb collisions at √sNN=2.76 TeV - Abelev, Betty; Angelov, Venelin; Bock, Friederike; Busch, Oliver; Fasel, Markus; Glässel, Peter; Grajcarek, Robert; Klein, Jochen; Kweon, MinJung; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; et al. (Physics letters, 2014)
The inclusive J/ψ nuclear modification factor (RAA) in Pb-Pb collisions at sNN=2.76 TeV has been measured by ALICE as a function of centrality in the e+e− decay channel at mid-rapidity (|y|<0.8) and as a function of centrality, transverse momentum and rapidity in the μ+μ− decay channel at forward-rapidity (2.5<y<4). The J/ψ yields measured in Pb-Pb are suppressed compared to those in pp collisions scaled by the number of binary collisions. The RAA integrated over a centrality range corresponding to 90% of the inelastic Pb-Pb cross section is 0.72±0.06(stat.)±0.10(syst.) at mid-rapidity and 0.58±0.01(stat.)±0.09(syst.) at forward-rapidity. At low transverse momentum, significantly larger values of RAA are measured at forward-rapidity compared to measurements at lower energy. These features suggest that a contribution to the J/ψ yield originates from charm quark (re)combination in the deconfined partonic medium.
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Im Titel steht "sNN" unter dem Wurzelsymbol und "NN" in sNN ist tiefgestellt
Gesehen am 11.08.2020